Zoonotic diseases awareness and food safety practices among livestock farmers in Nepal - Subedi, Deepak; Dhakal, Alok; Jyoti, Sumit; Paudel, Sanjay; Ranabhat, Ganesh; Tiwari, Ananda; Al-Mustapha, Ahmad I. (Frontiers in Veterinary Science, 2025)
Interactions between humans and livestock could increase the risk of zoonotic disease transmission. In addition, limited knowledge of zoonoses and foodborne diseases among livestock farmers could heighten the risks of foodborne illness and outbreaks of zoonotic diseases. This study evaluated the awareness of zoonotic diseases and preventive practices for zoonotic and foodborne diseases among livestock farmers of the Chitwan, Rupandehi, and Tanahun districts of Nepal by conducting a cross-sectional survey of 280 livestock farmers. They were recruited using the purposive sampling method from October to December 2022. Descriptive statistics revealed that most (72.1%; n = 202/280) livestock farmers were aware of zoonosis. None of the farmers knew about the zoonotic nature of leptospirosis. Two-thirds of pig farmers (67%; n = 12/18) were aware of zoonotic transmission of swine flu, and more than half of the poultry (58%; 50/86) farmers knew about zoonotic avian influenza. The majority of the farmers who had dogs (83%) and cats (89.4%) in their homes or farms knew that rabies can be transmitted to humans from dogs or cats. The multivariable logistic regression analysis revealed that farmers from the Rupandehi district (aOR: 5.56; 95% CI: 2.18–14.22) and Chitwan (aOR: 6.52; 95% CI: 2.46–17.25) had a higher odds of having good preventive practices than those from Tanahun. Also, farmers who had no sickness in the past 6 months after consumption of animal products were three times (aOR: 2.98; 95% CI: 1.48–6.01) more likely to have better practices. Furthermore, secondary education (aOR: 3.64; 95% CI: 1.41–9.44) was a significant positive predictor of good zoonotic diseases and food safety preventive practices. Our study underscores the necessity to enhance Nepalese livestock farmers’ awareness and practices regarding zoonotic and foodborne diseases. It emphasizes the importance of understanding risks, effective behavioral change strategies, and engaging farmers in developing zoonotic disease and foodborne illness prevention programs.